2009
DOI: 10.4049/jimmunol.0802994
|View full text |Cite
|
Sign up to set email alerts
|

Immature Dendritic Cell-Derived Exosomes Rescue Septic Animals Via Milk Fat Globule Epidermal Growth Factor VIII

Abstract: Sepsis, a highly lethal systemic inflammatory syndrome, is associated with increases of proinflammatory cytokines (e.g., TNF-α, HMGB1) and the accumulation of apoptotic cells that have the potential to be detrimental. Depending on the timing and tissue, prevention of apoptosis in sepsis is beneficial; however, thwarting the development of secondary necrosis through the active removal of apoptotic cells by phagocytosis may offer a novel anti-sepsis therapy. Immature dendritic cells (IDCs) release exosomes that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 46 publications
(54 reference statements)
5
105
1
2
Order By: Relevance
“…The blood level also was decreased by 45%, indicating the systemic scale of MFG-E8 depletion under septic condition (36). We also showed that LPS from Gramnegative bacteria, which play a pivotal role for the pathogenesis of CLP sepsis, downregulate this protein production from cultured RAW 264.7 macrophages (murine macrophage cell line) and peritoneal macrophages in vitro (31,35).…”
Section: Mfg-e8 Expression and Apoptotic Cell Clearance Are Suppressementioning
confidence: 75%
See 3 more Smart Citations
“…The blood level also was decreased by 45%, indicating the systemic scale of MFG-E8 depletion under septic condition (36). We also showed that LPS from Gramnegative bacteria, which play a pivotal role for the pathogenesis of CLP sepsis, downregulate this protein production from cultured RAW 264.7 macrophages (murine macrophage cell line) and peritoneal macrophages in vitro (31,35).…”
Section: Mfg-e8 Expression and Apoptotic Cell Clearance Are Suppressementioning
confidence: 75%
“…Besides LPS-CD14-TLR4 pathway, sepsis-derived apoptosis of immune cells as a source of MFG-E8 is suggested to be responsible for the depletion of MFG-E8 in sepsis (36). It also is reported that MFG-E8 is expressed constitutively in intestinal lamina propria macrophages of mice and CLP sepsis downregulates MFG-E8 production (10).…”
Section: Mfg-e8 Expression and Apoptotic Cell Clearance Are Suppressementioning
confidence: 98%
See 2 more Smart Citations
“…Importantly, exosomes from a variety of cell populations can mediate either immune activation or immune suppression based on the individual immunological microenvironment. [34][35][36][37] In autoimmunity, it has also been suggested that exosomes play a role in the chronic inflammatory response and that the cellular origin of exosomes will differentially influence the immune response in autoimmune disease. 6,38,39 Our data are important because they emphasize that co-stimulatory molecules play a pivotal role in APC-mediated immune responses, particularly T-cell activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%